Health service providers experience of psycho-emotional violence and associated factors among urban hospitals in Eastern Ethiopia - Tolera, Abebe; Weldesenbet, Adisu Birhanu; Regassa, Lemma Demissie; Tusa, Biruk Shalmeno; Merga, Bedasa Taye; Tariku, Mandaras; Cheru, Abera; Enyew, Daniel Birhanie; Gemeda, Assefa Tola (Frontiers in Public Health, 2024)
Background Psycho-emotional violence, a type of workplace violence targeting healthcare workers, varies across countries, occasions, and professions in the healthcare sector. Unfortunately, there is a scarcity of comprehensive studies focusing on violence against healthcare workers in Ethiopia, which may also encompass psycho-gender-based emotional violence against healthcare workers. Therefore, there is a compelling need for in-depth research to address this gap and develop effective strategies to mitigate psycho-emotional violence in the healthcare sector in Ethiopia, especially in the eastern region. Hence, we aimed to identify the prevalence of and factors associated with workplace psycho-emotional violence against healthcare providers in eastern Ethiopia. Methods This institution-based cross-sectional study was conducted among 744 health professionals working in urban public hospitals in eastern Ethiopia. Multistage stratified random sampling was used, and data were collected using a standardized structured tool adopted from the WHO workplace violence assessment tool. Binary and multivariable logistic regression analyses were employed to identify factors associated with psycho-emotional workplace violence. Adjusted odds ratio (OR) with 95% confidence interval (CI) was reported, and a p-value of 0.05 was used as the cut-off point to declare significance. Results Workplace psycho-emotional violence was reported by 57.39% of the healthcare workers. The absence of guidelines for gender-based abuse [AOR = 35.62, 95% CI:17.47, 72.64], presence of measures that improve surroundings (class lighting and privacy) [AOR = 0.58, 95% CI: 0.35, 0.98], training on workplace violence coping mechanism [AOR = 0.16, 95%CI: 0.26, 0.98], spending more than 50% of their time with HIV/AIDS patients [AOR = 1.96, 95%CI:1.05, 3.72], and spending more than 50% of their time with psychiatric patients [AOR = 1.92, 95%CI:1.08, 3.43] were factors significantly associated with workplace violence against health professionals. Conclusion The prevalence of workplace psycho-emotional violence against health professionals in eastern Ethiopia was relatively high. Improving the working environment decreases the chance of workplace violence; however, there is a lack of guidelines for gender-based violence, the absence of training on coping mechanisms, and spending more time with psychiatric and HIV/AIDS patients’ increases workplace violence. We recommend that health institutions develop gender abuse mitigation guidelines and provide training on coping mechanisms.